Phyogs thams cad las rnam par rgyal ba chen po ʼJam-mgon Sa-skya Paṇḍi-ta Kun-dgaʼ-rgyal-mtshan-dpal-bzaṅ-poʼi źabs kyi gsuṅ rab glegs bam daṅ po las Thub paʼi dgoṅs pa rab tu gsal ba źes bya baʼi bstan bcos bźugs so - Sa-skya Paṇḍi-ta Kun-dgaʼ-rgyal-mtshan, 1182-1251 (s.n., 1972)
Introduction (sṅon ʼgro) to Buddhist practice; a manual representing the approach of the Lamdray (Lam ʼbras) system of the Sakyapa tradition of Tibetan Lamaism.